Pendekatan Metode Utsmani: Strategi Efektif Meningkatkan Literasi Al-Qur'an di SD IT Menara Fitrah - mutiah; zainuddin; Noviani, Dwi (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research aims to find out how the Ottoman method can increase Al-Qur'an literacy at the Menara Fitrah IT Elementary School. The methods used in collecting data in this research were observation, interviews and documentation. The results of this research found that by using the Ottoman method students who do not yet know the hijaiyyah letters or who can read the Qur'an but have not yet mastered reading such as makhrojul letters or where the hijaiyyah letters come out and the properties of the letters, the students are given training and guidance continuously how to read the hijaiyyah letters with the correct reading, so that they are not only able to memorize the hijaiyyah letters and the reading of the Qur'an, but can pronounce them (mahrijul letters and character traits) according to good reading and recitation. So that after learning the Ottoman method, it is very influential so that students are able to read the Qur'an well and correctly according to the reading and the rules of recitation